Speech Acts Describing The Stage Of Self Acceptance In The Main Character In The Film Wonder (2017) - Andini, Lastri Andini; Sari Rejeki; Dyah Kristyowati (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2023)
Abstract: This study aims to identify the forms and types of illocutionary and perlocutionary speech acts that describe the stages of self-acceptance of the main character in the Wonder 2017 film. This research uses a qualitative approach with a descriptive method. The primary data source is taken from the main character’s speech, which reflects the stages of self-acceptance collected using the listening and note-taking methods. The results of this study include the following: 1) There are 15 utterances of the illocutionary act in the main character, assertives, and expressions are the dominant types is the most found. Perlocutionary speech acts are found with verbal, nonverbal, and verbal non-verbal types. 2) There are 5 stages of self-acceptance in the main character’s speech: phase 1 denial, phase 2 anger, phase 3 bargaining. Phase 4 depression, and phase 5 acceptance. From the five stages of self-acceptance, phase 2 of anger is the dominant type, specifically 6 utterances. 3) There are speech acts in this film that reflect the stages of self-acceptance in the main character who is going through a process of self-acceptance